PERLINDUNGAN HUKUM DAN ANALISIS POTENSI DESAIN INDUSTRI PADA EKONOMI KREATIF YANG BERBASIS ILMU PENGETAHUAN YANG DIHASILKAN OLEH UMKM DI KOTA PANGKALPINANG - Sigit Nugroho; Sujadmi Sujadmi (PROGRESIF: Jurnal Hukum, 2016)
Businesses creativity is needed in maintaining Indonesia's economy, especially in the field of industrial design, so that the resulting industrial design businesses in Indonesia can be protected. One measure that can boost the economy of a region is how much the intellectual property to protected and developed as a defense of wealth and the economy of a region or nation. The purpose this research is to analyze the legal protection and the potential for industrial design in the creative economy in Pangkalpinang. This research, using qualitative research with descriptive research strategy (descriptive research). Object in this research regarding legal protection and the potential for industrial design in the creative economy. From this research can be generated that design in the creative economy in Pangkalpinang not many. The resulting designs are still not adequately protected. Industrial designs in Pangkalpinang still have the potential to be featured as one proponent of the community's economy, especially in Pangkalpinang.